Cognitive flexibility moderates the relationship between openness-to-experience and perceptual reversals of Necker cube - Koivisto, Mika (Elsevier, 2025)
It is not clear whether personality is related to basic perceptual processes at the level of automatic bottom-up processes or controlled top-down processes. Two experiments examined how personality influences perceptual dynamics, focusing on how cognitive flexibility moderates the relationship between personality and perceptual reversals of the Necker cube. The participants viewed stimuli either passively or with the intent to either hold or switch the orientation of the Necker cube. The influence of openness was predominantly evident in conditions necessitating intentional control over perceptual reversals. The link between openness and intentional perceptual reversals was always moderated by cognitive flexibility, which was measured in three different ways. No relationship was detected between personality traits and reversals in the passive viewing condition, suggesting that relatively spontaneous adaptation-inhibition processes may not be personality-dependent. Overall, our research sheds light on the nuanced influence of personality traits on perceptual experiences, mediated by cognitive flexibility.